STRATEGY FOR THE MANAGEMENT OF MARINE RESOURCES AND COASTAL IN ISLA UVITA, LIMÓN, COSTA RICA - Pereira-Chaves, José (2009)
The Caribbean Coast of Costa Rica is known for its marine resource diversity, and is where the Uvita Island Insular System is located. This site was declared a National Monument in 1985, and chosen as the site for the present study, which had the main objective of offering an adequate managing tool to perform several conservation and sustainable development actions on the Island, to promote the coordination and participation of all stakeholders. The study clearly identified the need for developing a management strategy to promote pertinent conservation actions at the site, to strengthen not only its particular diversity, but also to establish educational and scientific regulations to encourage the adequate conditions for the sustainable development of the Island. Currently, the Island faces conservation and management problems due to the lack of an administrator to control and regulate the use of the site. In order to learn about the perception of the local people, a survey type questionnaire was administered and a workshop held at the site. Based on the results of the survey, the majority of the local people thought that the Island activities should be regulated and vigilance controls established. It was also well recognized that government institutions, such as MINAE and JAPDEVA, should manage the site with the support of the local government, which should acquire a commitment towards conservation. ºThe study proposed a management strategy for the Island, placing emphasis on six lines of action: institutional organization, protection, zoning, education and training, monitoring, and research and recreation.